Expression profiling of the Dof gene family under abiotic stresses in spinach - Hongying Yu (Nature Portfolio, 2021)
Abstract DNA-binding with one finger (Dof) are plant-specific transcription factors involved in numerous pathways of plant development, such as abiotic stresses responses. Although genome-wide analysis of Dof genes has been performed in many species, but these genes in spinach have not been analyzed yet. We performed a genome-wide analysis and characterization of Dof gene family in spinach (Spinacia oleracea L.). Twenty-two Dof genes were identified and classified into four groups with nine subgroups, which was further corroborated by gene structure and motif analyses. Ka/Ks analysis revealed that SoDofs were subjected to purifying selection. Using cis-acting elements analysis, SoDofs were involved in plant growth and development, plant hormones, and stress responses. Expression profiling demonstrated that SoDofs expressed in leaf and inflorescence, and responded to cold, heat, and drought stresses. SoDof22 expressed the highest level in male flowers and under cold stress. These results provided a genome-wide analysis of SoDof genes, their gender- and tissue-specific expression, and response to abiotic stresses. The knowledge and resources gained from these analyses will benefit spinach improvement.